Valorisation of walnut shell and pea pod as novel sources for the production of xylooligosaccharides. (1st July 2021) - Cebin, Aleksandra Vojvodić; Ralet, Marie-Christine; Vigouroux, Jacqueline; Karača, Sara; Martinić, Arijana; Komes, Draženka; Bonnin, Estelle
Graphical abstract: Highlights: Walnut shell (WS) and pea pod (PP) are underutilized sources of xylan. Xylan is present as low branched 4- O -methyl-glucuronoxylan and/or arabinoglucuronoxylan. Delignificatinon had a major effect on xylan extractability from WS and PP. Hydrolysis by GH11 endo -xylanase generated mostly xylose, xylobiose and xylotriose. Xylan conversion and XOS profile varied with enzyme concentration and hydrolysis time. Abstract: According to the high interest in agro-industrial waste reutilisation, underutilised lignocellulosic materials, such as walnut shell (WS) and pea pod (PP), come in focus. The aim of this paper was to evaluate WS and PP as sources for the production of xylooligosaccharides (XOS). Hemicelluloses from WS and PP were recovered by combining varying parameters of delignification and alkaline extraction. At optimal recovery conditions, the fractions were further hydrolysed to XOS using GH11 endo -xylanase, by varying time and enzyme concentration. Xylose was predominant in the monomeric composition of the obtained hemicelluloses, building low-branched (arabino)glucuronoxylan, in WS exclusively, while in PP some xyloglucan as well. Delignification was essential for high recovery of total xylose from the materials, up to at least 70 %. High xylan conversions were obtained for 24 h hydrolysis, resulting in xylobiose and xylotriose when using low enzyme concentration, while in xylose and xylobiose with high enzyme concentration.